Family Financial Literacy Training in Beji, Depok - Febriantina, Susan; Susita, Dewi; Saparuddin; Sholikhah; Zakaria, Adam; Fadillah, Nadya; Rahmi; Pratama, Aditya; Sasmi, Aji Ahmadi; Malzara, Vidia Ratu Balqis; Azalia, Farah Cantika (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Community empowerment, especially for the lower middle class, needs to be done to reduce unemployment and improve welfare. Weak family financial literacy is one of the fundamental problems. This community service team intends to provide solutions to the above problems, namely in the form of family financial literacy training. The target of this empowerment is housewives whose economic status is lower middle class in Beji Village, Beji District, Depok City, West Java. The training material is presented in the form of material presentations by resource persons, followed by discussion. This community service activity proved to be able to provide an understanding of financial planning for the participants who were members of the Baitussalam Healthy and Fit Community in Beji Village, Depok City.